Earthquake synchrony and clustering on Fucino faults (Central Italy) as revealed from in situ 36Cl exposure dating. Issue 9 (6th September 2013) - Benedetti, Lucilla; Manighetti, Isabelle; Gaudemer, Yves; Finkel, Robert; Malavieille, Jacques; Pou, Khemrak; Arnold, Maurice; Aumaître, Georges; Bourlès, Didier; Keddadouche, Karim
Abstract: [1] We recover the Holocene earthquake history of seven seismogenic normal faults in the Fucino system, central Italy. We collected 800 samples from the well‐preserved limestone scarps of the faults and modeled their 36 Cl concentrations to derive their seismic exhumation history. We found that > 30 large earthquakes broke the faults in synchrony over the last 12 ka. The seven faults released strain at the same periods of time, 12–9 ka, 5–3 ka, and 1.5–1 ka. On all faults, the strain accumulation and release occurred in 3–6 ka supercycles, each included a 3–5 ka phase of slow (≤ 0.5–2 mm/yr) strain accumulation in relative quiescence, followed by a cluster of three to four large earthquakes or earthquake sequences that released most of the strain in < 1–2 ka. The large earthquakes repeated every 0.5 ± 0.3 ka during the paroxysmal phases and every 4.3 ± 0.9 ka between those phases. Earthquakes on the northern faults produced twice larger surface slips ( 2 m) and had larger magnitudes (Mw 6.2–6.7) than those on the southern faults. On most faults, the relative strain level was found to control the amount of slip and the time of occurrence of the next large earthquake. Faults entered a phase of clustered activity once they had reached a specific relative strain threshold. The Tre Monti fault is identified as the most prone to break over the next century. Our data document earthquake synchrony and clustering at a broader space and time scale than has been reported to date. Key Points: Earthquake history of seven normal faults is recovered with 36Cl exposure dating Earthquake clustering seen at broader scale and longer time than ever observed 30 large earthquakes broke the faults in synchrony over the last 12 ka